Local structure analysis of (Na0.5K0.45Li0.05)NbO3 synthesized by malic acid complex solution method. (20th September 2017) - Yoneda, Yasuhiro; Takada, Eri; Nagai, Haruka; Kikuchi, Takeyuki; Morishita, Masao; Kobune, Masafumi
Abstract: A monoclinic ferroelectric phase with the space group Pm has been discovered in lead-free (Na0.5 K0.45 Li0.05 )NbO3 solid solution ceramics synthesized by a malic acid complex solution method. At ambient temperature, the lattice parameters of this monoclinic structure were . The average and local structures of this monoclinic phase were analyzed by synchrotron X-ray measurements. The average structure maintained the monoclinic structure down to 20 K, although the local structure changed below room temperature. The distinct short-range order structure was found to be rhombohedral. The results demonstrate the presence of an order–disorder-type phase transition structurally bridging between the rhombohedral local structure and the low-symmetry monoclinic average structure in a (Na0.5 K0.45 Li0.05 )NbO3 solid solution system.